2016
DOI: 10.1080/2162402x.2016.1213932
|View full text |Cite
|
Sign up to set email alerts
|

CD1b-autoreactive T cells recognize phospholipid antigens and contribute to antitumor immunity against a CD1b+T cell lymphoma

Abstract: Adoptive immunotherapy for cancer treatment is an emerging field of study. Till now, several tumorderived, peptide-specific T cell responses have been harnessed for treating cancers. However, the contribution of lipid-specific T cells in tumor immunity has been understudied. CD1 molecules, which present self-and foreign lipid antigens to T cells, are divided into group 1 (CD1a, CD1b, and CD1c) and group 2 (CD1d). Although the role of CD1d-restricted natural killer T cells (NKT) in several tumor models has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…CD1b-autoreactive HJ1 T cells were enriched in the liver and exhibited an activated/effector phenotype (CD44 hi , CD69 + , CD122 + ) in the naïve setting ( 97 ). Additionally, HJ1 T cells were shown to be protective against Listeria monocytogenes infection ( 97 ) and contribute to antitumor immunity against a CD1b + T cell lymphoma ( 97 , 98 ). In a recent study, we also demonstrated that under conditions of hyperlipidemia, HJ1 T cells contributed to the development of an inflammatory psoriasis-like skin inflammation ( 23 ).…”
Section: Cd1-restricted T Cellsmentioning
confidence: 99%
“…CD1b-autoreactive HJ1 T cells were enriched in the liver and exhibited an activated/effector phenotype (CD44 hi , CD69 + , CD122 + ) in the naïve setting ( 97 ). Additionally, HJ1 T cells were shown to be protective against Listeria monocytogenes infection ( 97 ) and contribute to antitumor immunity against a CD1b + T cell lymphoma ( 97 , 98 ). In a recent study, we also demonstrated that under conditions of hyperlipidemia, HJ1 T cells contributed to the development of an inflammatory psoriasis-like skin inflammation ( 23 ).…”
Section: Cd1-restricted T Cellsmentioning
confidence: 99%
“…To identify self-lipids presented by CD1b to HJ1 T cells, CD1b plate-bound assays were performed. In a previous study, we have shown that HJ1 T cells cannot be activated by different species of ceramides (46). Commercially purchased polar lipid extract, cholesterol, and fatty acid mixtures were loaded onto purified CD1b protein, coated onto 96-well plates, and cultured with HJ1 hybridoma cells.…”
Section: The Expression Of Costimulatory Molecule Cd86 On Cd1b-expresmentioning
confidence: 99%
“…The TCRs of invariant natural killer T‐cells for example, predominantly bind CD1d, whereas the polar head group of the lipid modulates the interaction. Moreover, recent reports suggest that ligands bound to CD1 can modulate TCR interaction even when they are not contacted directly by the TCR . Here we describe the possible modes of recognition of CD1 by T‐cells and mechanisms behind the range of activity that T‐cells display to CD1 antigens.…”
Section: Diverse Mechanisms Of Antigen Display To T‐cellsmentioning
confidence: 90%
“…A role for CD1b‐restricted T‐cells in cancer has only recently been shown, which is highlighted in the double transgenic mouse model that expresses human group 1 CD1 molecules and the CD1b autoreactive HJ1 TCR. The CD1b autoreactive HJ1 T‐cells recognized several self phospholipids that are known to accumulate in tumours including phosphatidylethanolamine, phosphatidylglycerol, ether‐linked phosphatidylethanolamine, phosphatidylcholine and phosphatidylinositol . HJ1 T‐cells were more potently activated by tumour‐derived self‐lipids than those isolated from healthy cells and were able to kill CD1b‐expressing tumours.…”
Section: Group 1 Cd1 Elicit T‐cell Responses In a Variety Of Disease mentioning
confidence: 99%